Kemampuan Menganalisis Makna Tersirat Struktur Teks Hikayat “Si Miskin” Siswa Kelas X SMA Muhammadiyah 1 UNISMUH Makassar (International Forum of Researchers and Lecturers, 2023)
The aim of this study is to find out the ability to analyze the implied meaning of the text structure of the saga